2022
DOI: 10.21203/rs.3.rs-1211312/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Sulfavant A as the First Synthetic TREM2 Ligand Discloses a Homeostatic Response of Dendritic Cells After Receptor Engagement

Abstract: The immune response arises from a fine balance of cellular and molecular mechanisms that provide for surveillance, tolerance, and elimination of dangers as pathogens. Improving the quality of the immune response remains a major goal in immunotherapy and vaccine development. Sulfavant A (SULF A) is a sulfolipid that has shown promising adjuvant activity in a cancer vaccine model. Here we report that SULF A is the first synthetic small molecule binding to the Triggering Receptor Expressed on Myeloid cells-2 (TRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The product was tested as adjuvant in an experimental model of tumor vaccine against a murine B16F10 melanoma cell line with very encouraging results [176]. Recent studies on the mechanism of action indicated that SULF A is a ligand of the Triggering Receptor Expressed on Myeloid cells-2 (TREM2) [177]. The TREM2-iduced response is mediated by SYK-NFAT axis and is compromised by blockade and gene silencing of the receptor.…”
Section: Compounds From Marine Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The product was tested as adjuvant in an experimental model of tumor vaccine against a murine B16F10 melanoma cell line with very encouraging results [176]. Recent studies on the mechanism of action indicated that SULF A is a ligand of the Triggering Receptor Expressed on Myeloid cells-2 (TREM2) [177]. The TREM2-iduced response is mediated by SYK-NFAT axis and is compromised by blockade and gene silencing of the receptor.…”
Section: Compounds From Marine Environmentmentioning
confidence: 99%
“…The TREM2-iduced response is mediated by SYK-NFAT axis and is compromised by blockade and gene silencing of the receptor. Activation by this lipid preserved the DC functions to excite the allogeneic T cell response and promoted interleukin-10 (IL-10) release after lipopolysaccharide (LPS) stimulation [177].…”
Section: Compounds From Marine Environmentmentioning
confidence: 99%